Bestimmung zeitabhängiger Blutdruckfelder aus Strömungsdaten der Magnetresonanztomographie - Delles, Michael (KIT Scientific Publishing, 2015)
In cardiovascular diagnostics, blood pressure computation from flow data acquired by magnetic resonance imaging is considered promising. Accordingly, this work describes a method for the computation of complete spatiotemporal blood pressure fields in the human aorta. Key issues are the robust pressure computation from noisy input data, the application of regularized blood flow models, the combination of spatial and temporal blood pressure information, and the experimental evaluation.